I sank the Bismarck - Moffat, John; Rossiter, Mike (Bantam, 2009)
In the early hours of 27th May, 1941, Fleet Air Arm pilot John Moffat took to the air in his open cockpit bomber. Along with 12 other brave pilots, he took down the German warship Bismarck - a warship that had destroyed the famed HMS Hood. This is his story. John Moffat tells of everything that led him to be able to say, 'I sank the Bismarck'